Digital Marketing Strategy: Create Strategy, Put it into Practice, Sell More - Lahtinen, Niko; Pulkka, Kimmo; Karjaluoto, Heikki; Mero, Joel (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar Publishing, 2023)
"This cutting-edge book presents a detailed overview of digital marketing strategy, which has evolved following rapid digitalization that occurred during the COVID-19 pandemic. Providing detailed examinations of different digital marketing techniques, it demonstrates how organizations' digital marketing strategies can be developed and implemented. Digital Marketing Strategy features a thorough analysis of how digital marketing can be utilized to increase sales through new customer acquisition and through increasing the life cycle value of its existing customers. Chapters explore how buyer personas can be used to frame marketing as an advantageous service. Ultimately, this instructive book highlights that the core of digital marketing is based on market analysis, the value proposition built on it, and observed competitive advantage. With fresh insights into the developing areas of content and influencer marketing, this book will be of immense worth to students and scholars studying digital marketing strategy. It will also be highly applicable to those working in the field of digital marketing who promote products and services that require buyer judgement"--
Includes bibliographical references (pages 143-147) and index.
Keywords: Internet marketing; Digital media; Marketing